The antebellum press
1 online resource
Keywords: The Antebellum Press: Setting the Stage for Civil War reveals the critical role of journalism in the years leading up to America's deadliest conflict by exploring the events that foreshadowed and, in some ways, contributed directly to the outbreak of war. This collection of scholarly essays traces how the national press influenced and shaped America's path towards warfare. Major challenges faced by American newspapers prior to secession and war are explored, including: the economic development of the press; technology and its influence on the press; major editors and reporters (North and South) and the role of partisanship; and the central debate over slavery in the future of an expanding nation. A clear narrative of institutional, political, and cultural tensions between 1820 and 1861 is presented through the contributors' use of primary sources. In this way, the reader is offered contemporary perspectives that provide unique insights into which local or national issues were pivotal to the writers whose words informed and influenced the people of the time. As a scholarly work written by educators, this volume is an essential text for both upper-level undergraduates and postgraduates who study the American Civil War, journalism, print and media culture, and mass communication history.